A novel cell‐based sensor detecting the activity of individual basic proprotein convertases. (24th July 2019) - Löw, Karin; Hardes, Kornelia; Fedeli, Chiara; Seidah, Nabil G.; Constam, Daniel B.; Pasquato, Antonella; Steinmetzer, Torsten; Roulin, Alexandre; Kunz, Stefan
Abstract : The basic proprotein convertases (PCs) furin, PC1/3, PC2, PC5/6, PACE4, PC4, and PC7 are promising drug targets for human diseases. However, developing selective inhibitors remains challenging due to overlapping substrate recognition motifs and limited structural information. Classical drug screening approaches for basic PC inhibitors involve homogeneous biochemical assays using soluble recombinant enzymes combined with fluorogenic substrate peptides that may not accurately recapitulate the complex cellular context of the basic PC–substrate interaction. Herein we report basic PC sensor (BPCS), a novel cell‐based molecular sensor that allows rapid screening of candidate inhibitors and their selectivity toward individual basic PCs within mammalian cells. BPCS consists of Gaussia luciferase linked to a sortilin‐1 membrane anchor via a cleavage motif that allows efficient release of luciferase specifically if individual basic PCs are provided in the same membrane. Screening of selected candidate peptidomimetic inhibitors revealed that BPCS can readily distinguish between general and selective PC inhibitors in a high‐throughput screening format. The robust and cost‐effective assay format of BPCS makes it suitable to identify novel specific small‐molecule inhibitors against basic PCs for therapeutic application. Its cell‐based nature will allow screening for drug targets in addition to the catalytically active mature enzyme, including maturation, transport, and cellular factors that modulate the enzyme's activity. This broadened 'target range' will enhance the likelihood to identify novel small‐molecule compounds that inhibit basic PCs in a direct or indirect manner and represents a conceptual advantage. Abstract : The basic proprotein convertases (PCs) are promising drug targets for human diseases. However, developing selective inhibitors remains challenging due to overlapping substrate recognition motifs and limited structural information. Here, we report a novel cell‐based basic PC sensor that allows rapid screening of candidate inhibitors and their selectivity toward individual basic PCs within mammalian cells and is suitable for high‐throughput screening.